2018
DOI: 10.1093/ndt/gfy027
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine on microparticles and associated cells contributes to the hypercoagulable state in diabetic kidney disease

Abstract: Our results suggest that PS+ MPs and MP-origin cells play procoagulant roles in patients with DKD. Blockade of PS could become a novel therapeutic modality for the prevention of thrombosis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Uremic toxins constitute the central one. To support, the PS + EV levels in vivo are inversely correlated with the glomerular filtration rate (Almquist et al, 2016;Yu et al, 2018), but positively with uric acid and proteinuria levels (Yu et al, 2018). More procoagulant MVs are detected in diabetes mellitus patients with CKD compared to patients without it (Almquist et al, 2016), and in patients with extreme albuminuria than in those with lower or normal levels (Yu et al, 2018).…”
Section: Evs In the Plasma Of Ckd Patients: General Outline Of Our Knmentioning
confidence: 91%
See 2 more Smart Citations
“…Uremic toxins constitute the central one. To support, the PS + EV levels in vivo are inversely correlated with the glomerular filtration rate (Almquist et al, 2016;Yu et al, 2018), but positively with uric acid and proteinuria levels (Yu et al, 2018). More procoagulant MVs are detected in diabetes mellitus patients with CKD compared to patients without it (Almquist et al, 2016), and in patients with extreme albuminuria than in those with lower or normal levels (Yu et al, 2018).…”
Section: Evs In the Plasma Of Ckd Patients: General Outline Of Our Knmentioning
confidence: 91%
“…To support, the PS + EV levels in vivo are inversely correlated with the glomerular filtration rate (Almquist et al, 2016;Yu et al, 2018), but positively with uric acid and proteinuria levels (Yu et al, 2018). More procoagulant MVs are detected in diabetes mellitus patients with CKD compared to patients without it (Almquist et al, 2016), and in patients with extreme albuminuria than in those with lower or normal levels (Yu et al, 2018). To get a laboratory verification, incubation of normal endothelial cells or red blood cells (RBCs) with (i) patients' serum, (ii) uremic toxins at concentrations found in patients, or (iii) increased concentration of phosphate induce PS exposure on cells and EVs release (Faure et al, 2006;Abbasian et al, 2015;Gao et al, 2015a,b;Yu et al, 2018).…”
Section: Evs In the Plasma Of Ckd Patients: General Outline Of Our Knmentioning
confidence: 99%
See 1 more Smart Citation
“…PtdSer has been detected in microparticles in blood that have been implicated in hypercoagulation in diabetic kidney disease (Yu et al, 2018), cancer (Lea et al, 2017; Liu et al, 2019; Zhao et al, 2016), and inflammation (Zhao et al, 2016). Whether PtdSer is also an integral component of lipoproteins in humans is not known.…”
Section: Discussionmentioning
confidence: 99%
“…circulating MPs are produced by a variety of cells, such as erythrocytes, granulocytes, monocytes, platelets, and endothelial cells (38). In recent years, studies have found that MPs induce hypercoagulability in a number of diseases, such as sepsis, stroke and nephrotic syndrome (39,40). The expression of phosphatidylserine (PS) is the underlying cause of MP-induced coagulation.…”
Section: Mps and Hypercoagulabilitymentioning
confidence: 99%